Экспериментальное заражение рыб свободноплавающими церкариями кошачьей двуустки (Opisthorchis felineus RIV.) - Близнюк, И.Д. (Вестник зоологии, 1969)
In the experiments fish of different species was infected with cercarii Opisthorchis felineus. The following fish of the Cyprinidae family proved to be susceptible to the infection: various races of Cyprinus carpio, Carassius carassius, C. aureus, Rutilus rutilus. Tinea tinea, Alburnus alburnus and Gobio fluviatilis. Cercarii did not penetrate into the body of Esox lucius and Perea fluviatilis. The efficiency of infection depends on the fish age. Cercarii can penetrate through the skin only into the body of fish at the initial stages of development, their infection is of total character. Character in fish of one year and older ones cercarii can penetrate only into fins, gills, mouth cavity and the wall of the upper part of the alimentary canal, where they become encysted. Cercarii 0. felineus penetrate into the fish organism mainly at the early stages of their life, up to the stage of fry inclused. Superinvasion at the following stages of fish development does not increase substantially the intensity of their infection.